Understanding the role of vitamin A and its precursors in the immune system - AKTAÇ, ŞULE (My University, 2022)
Vitamin A is the first defined vitamin and is also known as an anti-inflammatory micronutrient. Although the primary biological function is preservation of epithelial tissue integrity, vision and growth, vitamin A also plays a role in immune system regulation. It is known that susceptibility to infections increases in developing countries due to vitamin A deficiency. Therefore, the purpose of this review is to evaluate the role of vitamin A on the immune system in line with current studies. In this review, we focused on the immunobiological effects of vitamin A and its precursors. Vitamin A refers to retinoids and carotenoids, but both function in the body through the most active form, all trans retinoic acid. All trans retinoic acid has the highest affinity of nuclear retinoic acid receptor. Reports from in-vivo and in-vitro studies shown that the formation of retinoic acid/retinoic acid receptor complex is important in the generation of innate and adaptive immune cell response. In addition to immune cell response, vitamin A also plays an important role in mucus secretion, morphological formation and functional maturation of epithelial cells. In this way, vitamin A appears to contribute to immune development by regulating immune cell response and providing mechanistic defense. Vitamin A has received particular attention in recent years as the vitamin have been shown to have a crucial effect on the immune response. Although more randomized controlled studies are needed, data from observational human studies have shown that vitamin A is associated with infectious, inflammatory, allergic diseases and cancers. ?? 2021 Published by Elsevier Masson SAS on behalf of Soci??t?? francophone nutrition clinique et m??tabolisme (SFNCM).
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Beslenme ve Dietetik; Tarımsal Bilimler; Ziraat; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Nutrition and Dietetics; Agricultural Sciences; Agriculture; ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); BESLENME VE DİYETETİK; Tarım Bilimleri; Tarım ve Çevre Bilimleri (AGE); ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); NUTRITION & DIETETICS; AGRICULTURAL SCIENCES; Agriculture & Environment Sciences (AGE); Endokrinoloji; Endokrin ve Otonom Sistemler; Beslenme ve Diyetetik; Endokrinoloji, Diyabet ve Metabolizma; Yaşam Bilimleri; Endocrinology; Endocrine and Autonomic Systems; Endocrinology, Diabetes and Metabolism; Life Sciences; Retinol; Retinoic acid; Carotenoid; Immune system; TRANS-RETINOIC ACID; INTESTINAL EPITHELIAL-CELLS; INNATE LYMPHOID-CELLS; TRETINOIN 0.05-PERCENT LOTION; SEVERE ACNE-VULGARIS; ONCE-DAILY TREATMENT; REGULATORY T-CELLS; RAT-LIVER; INTERFERON-GAMMA; GENE-EXPRESSION